How the Menstrual Cycle Can Be Utilized During Sports Training, Performance, and Recovery through Wearable Technology: A Narrative Review for Researchers, Physicians, Coaches, and Athletes - Hunter, Naiomi Nhen; Smith, Morgan A. (Seminars in Reproductive Medicine, 2024)
The menstrual cycle (MC) serves as a vital indicator of overall health and metabolic function, regulated by the hypothalamic–pituitary axis and involving a complex interplay of hormones. Understanding these hormonal dynamics is crucial for deciphering an individual's physiological status and performance potential, particularly in athletes. Studies regarding the MC's impact on athletic performance and training often lack inclusivity, standardized methodologies, and inconsistent biological definitions, hindering comprehensive conclusions. Moreover, societal inequalities contribute to the underrepresentation of female athletes in research, exacerbating the lack of understanding regarding female physiology in sports medicine. Leveraging wearable technology presents a promising avenue for both tracking MCs and optimizing athletic training/recovery. Wearables offer real-time monitoring of biometrics that often correlate with hormonal fluctuations, and lifestyle trends (diet, sleep, stress) aiding in personalized training schedules and performance optimization. Integrating data collected by MC dynamics and wearable technology into athletic training has the potential to decrease the generally perceived negative impacts MC has on athletic performance. Addressing gaps in research methodologies and promoting awareness among athletes, coaches, and healthcare professionals are essential steps toward maximizing the potential of MC-informed training strategies.
Keywords: menstrual cycle; athletics; wearable technology; female biology